Implementation of Good Governance in Public Services at Local Government - Adelia Azzahra (International Journal of Social Service and Research, 2023)
This research is motivated by the suboptimal public services provided by government officials in XYZ District. The primary goal of this study is to evaluate the government's execution of good governance principles to enhance public services in the area. The key elements of good governance include accountability, transparency, openness, and adherence to the rule of law. The research employs a descriptive qualitative methodology and focuses on XYZ District as the research location. Data is collected through literature review and field study, with data validity testing conducted using triangulation techniques. The research findings indicate that the implementation of good governance in public service improvement is characterized by accountability, ensuring officials follow standard implementation procedures; transparency, making public interest information readily available to citizens; openness, providing services without discrimination to all citizens; and adherence to the rule of law, ensuring fair service delivery in line with applicable laws.